Synthesis of functionalized 6-hydroxy-2-oxindole derivatives by phenoxide cyclization - Reddy, B. Narendraprasad; Ramana, Chepuri V. (Organic Letters, 2016)
An apparent intramolecular cross-dehydrogenative coupling of N-(3-hydrox)monoanilide of maleic esters comprising base promoted phenoxide cyclization and subsequent base-mediated aerobic oxidation was developed to synthesize a variety of 2-(6-hydroxy-2-oxoindolin-3-ylidene)-acetate derivatives. The isolation of intermediate cyclized products during the large scale reactions and their ready dehydrogenation with 1 equiv of base support this proposed two-step path.